Connexin36 Expression in Primary Afferent Neurons in Relation to the Axon Reflex and Modality Coding of Somatic Sensation. (15th July 2018) - Nagy, J.I.; Lynn, B.D.; Senecal, J.M.M.; Stecina, K.
Graphical abstract: Highlights: eGFP serves as a reporter for connexin36 expression in sensory ganglia. Wide expression of eGFP is found in some but not all modality-defined sensory neurons. Connexin36 protein is detected in fibers of peripheral nerves. Primary afferent nociceptive fibers have the highest potential for electrical coupling. Abstract: Electrical coupling mediated by connexin36-containing gap junctions that form electrical synapses is known to be prevalent in the central nervous system, but such coupling was long ago reported also to occur between cutaneous sensory fibers. Here, we provide evidence supporting the capability of primary afferent fibers to engage in electrical coupling. In transgenic mice with enhanced green fluorescent protein (eGFP) serving as a reporter for connexin36 expression, immunofluorescence labeling of eGFP was found in subpopulations of neurons in lumbar dorsal root and trigeminal sensory ganglia, and in fibers within peripheral nerves and tissues. Immunolabeling of connexin36 was robust in the sciatic nerve, weaker in sensory ganglia than in peripheral nerve, and absent in these tissues from Cx36 null mice. Connexin36 mRNA was detected in ganglia from wild-type mice, but not in those from Cx36 null mice. Labeling of eGFP was localized within a subpopulation of ganglion cells containing substance P and calcitonin gene-releasing peptide, and in peripheral fibers containing these peptides. Expression of eGFP was also found in various proportions of sensory ganglion neurons containing transient receptor potential (TRP) channels, including TRPV1 and TRPM8. Ganglion cells labeled for isolectin B4 and tyrosine hydroxylase displayed very little co-localization with eGFP. Our results suggest that previously observed electrical coupling between peripheral sensory fibers occurs via electrical synapses formed by Cx36-containing gap junctions, and that some degree of selectivity in the extent of electrical coupling may occur between fibers belonging to subpopulations of sensory neurons identified according to their sensory modality responsiveness.